Une note sur Ipouer XII, 13–14 - Winand, Jean (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
This paper is a reanalysis of a well known passage of the Admonitions (XII, 13–14). After reviewing the previous studies, the first conclusion that can be drawn is that the translations that have been proposed so far never meet the double criterion of grammatical correctness and sound contextual meaning. To reconcile these two points of view, it is here first suggested that jn-jw , which stands at the beginning of the sentence, experienced a process of lexicalisation ( jn-jw ø “what does it mean, a shepherd who loves death?”). A second option would be to consider mnjw as the predicate of a subjectless nominal sentence ( À ø “is that really a shepherd, the one who loves death?”).